2011
DOI: 10.1080/19768354.2011.604941
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypoosmotic and thermal stress on gene expression and the activity of antioxidant enzymes in the cinnamon clownfish,Amphiprion melanopus

Abstract: We studied oxidative stress in cinnamon clownfish exposed to hypoosmotic (35 psu 0 17.5 psu and 17.5 psu with prolactin (PRL)) and low temperature (288C 0 248C and 208C) conditions by measuring the expression and activity of Cu/Zn-superoxide dismutase (Cu/Zn-SOD), catalase (CAT), and glutathione peroxidase (GPX). The expression and activity of the antioxidant enzymes were significantly higher after the fish were exposed to 248C, 208C, and 17.5 psu, and expression was repressed by PRL treatment. Furthermore, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Particularly, the expression of cat was significantly higher in liver with high levels of vitamins E, C and K. Accordingly with these results, Mahmoud et al (2016) observed that the activity of CAT was influenced by the level of dietary vitamin C in Pagrus major. It has been observed in several studies a correlation between the mRNA expression levels and the activity of antioxidant enzymes (An et al, 2010;Penglase et al, 2010;Shin et al, 2010;Park et al, 2011). In the present study, sod and gpx expression showed a tendency to increase with high levels of vitamins in the diet, albeit not significantly.…”
Section: Discussionsupporting
confidence: 59%
“…Particularly, the expression of cat was significantly higher in liver with high levels of vitamins E, C and K. Accordingly with these results, Mahmoud et al (2016) observed that the activity of CAT was influenced by the level of dietary vitamin C in Pagrus major. It has been observed in several studies a correlation between the mRNA expression levels and the activity of antioxidant enzymes (An et al, 2010;Penglase et al, 2010;Shin et al, 2010;Park et al, 2011). In the present study, sod and gpx expression showed a tendency to increase with high levels of vitamins in the diet, albeit not significantly.…”
Section: Discussionsupporting
confidence: 59%
“…In the cinnamon clownfish (Amphiprion melanopus), enzyme activities of SOD, CAT, and glutathione peroxidase (GPx) were upregulated during two days of hypoosmotic challenge (Park et al, 2011). In the rainbow trout (Oncorhynchus mykiss), hepatic CAT activity elevated but SOD activity did not change under two-days hypoosmotic challenge (Blewett et al, 2017).…”
Section: Antioxidant Responses To Hypoosmotic Transfermentioning
confidence: 99%
“…Zebrafish cold shocked for up to 24 h (28 to 12°C) exhibited signs of oxidative stress and elevated antioxidant enzyme activity (CAT, GPx) and apoptosis rates in the gills and liver compared to an ambient control group (Wu et al ., 2015). Cinnamon clownfish ( Amphiprion melanopus Bleeker 1852) acclimatized to 28°C and cold stressed via gradual temperature reduction to 20°C (1°C per day) exhibited higher levels of H 2 O 2 and malondialdehyde (MDA; both indicators of oxidative stress) as well as slight increases in the expression of antioxidant enzymes (CAT, GPx and SOD; Park et al ., 2011). In GIFT tilapia head kidney tissues, lysozyme and SOD activity decreased, and MDA concentrations increased, over 96 h of cold shock (28 to 9.4°C) relative to an ambient control (Qiang et al ., 2018).…”
Section: Cold Stress and The Generalized Stress Response In Fishmentioning
confidence: 99%